Exploring the Role of Practice Managers in Dutch Oral Healthcare Practices - Joost CL den Boer; Wil JM van der Sanden; Katarina Jerković-Ćosić; Josef JM Bruers (International Dental Journal)
Introduction and aims: The practice manager (PM) is a familiar position in Dutch oral healthcare. However, little is known about in which type of practice they work and what their responsibilities are. The aims of this study were to analyse the characteristics of oral healthcare practices that employ a PM and practices that do not, to determine responsibility for tasks described in the PM function description, and to assess to what extent the role of a PM varies between those with an oral healthcare and another background, and across practices with different characteristics. Methods: At the end of 2022, a questionnaire with questions about the employment of a PM in the practice was presented to 991 randomly selected general dental practitioners. The questions about the tasks of the PM were based on the job description of the PM drawn up by the Royal Dutch Dental Association. Data were analysed using chi-square test, one-way ANOVA, linear regression, and logistic regression analyses. Results: A PM was employed in the practice of 56% of the general dental practitioners. In many cases, this PM was responsible for a large number of tasks within the sub-areas of care process, human resources, operational policy, and communication. Compared to independent practices, practices affiliated with a corporate dental company often employed a PM and the PMs had a relatively large amount of responsibility. Conclusion: PMs are now commonly found in Dutch oral healthcare practices, especially in ones that are affiliated with a corporate dental company. The tasks of PMs vary, suggesting an evolving professional profile.